Cloud and fog deposition: Monitoring in high elevation and coastal ecosystems. The past, present, and future. (1st April 2022) - Isil, Selma; Collett, Jeffery; Lynch, Jason; Weiss-Penzias, Peter; Rogers, Christopher M.
Abstract: Deposition of pollutants by cloud water exceeds deposition by precipitation and dry deposition in many high elevation settings. This larger loading of pollutants in these environments is due to a combination of factors such as high frequency of cloud immersion, high wind speeds, orographic enhancement of precipitation, and large leaf area of tree species typical in these environments. Fog-impacted coastal ecosystems also experience increased pollutant deposition similar to cloud-impacted high elevation sites. Therefore, development of meaningful critical load values and total nitrogen budgets for high-elevation and fog-impacted sites requires reliable cloud and fog water deposition estimates. The cost and labor intensity of cloud/fog water sample collection have made it difficult to conduct long-term studies that would provide the data needed to develop accurate estimates. Current understanding of fog formation, transport, and the role of fog and cloud deposition in hydrogeological and biogeochemical cycles is incomplete due, in part, to lack of a concerted interdisciplinary approach to the problem. Historically, these obstacles have limited interest in and collection of cloud and fog water samples. In addition to measurements of cloud/fog chemical composition, documenting fog/cloud deposition fluxes of pollutant and nutrient species requires knowledge of cloud/fog physical properties, frequency and duration of fog/cloud interception with landscapes, properties of vegetation on those landscapes, and properties of the wind that drive droplet/vegetation interactions. Because drop deposition efficiency is dependent on drop size, it is also important to consider variations in fog/cloud drop composition with drop size as species enriched in larger/smaller drops will experience enhanced/reduced deposition rates. This paper presents summary results from a small U.S. cloud water monitoring network that operated from the mid-nineties through 2011, as well as a brief qualitative review of other cloud and fog water studies conducted in the United States (including Puerto Rico), Europe, South America/Pacific, and Asia. Current collection methods are also reviewed. Recent scientific efforts by the National Atmospheric Deposition Program's (NADP) Total Deposition Science Committee and NADP's Critical Loads of Atmospheric Deposition Science Committee have identified occult (cloud/fog) deposition as a "need" in developing critical loads for ecosystems that experience significant cloud and fog impaction. To this end, remaining knowledge gaps and suggestions for future research to investigate these gaps are explored. Highlights: At elevations above 800m cloud water samples are usually 5–20 times more acidic than rainwater. Impacts of N deposition on alpine/subalpine regions are numerous and substantial. Deposition loads of 10–40 kg N/ha/year in high-elevation areas in the eastern US are much higher than in the west. Productivity and species shifts may have already occurred in eastern alpine ecosystems. This paper is a qualitative summary of existing knowledge on cloud/fog water deposition.